2017
DOI: 10.5430/jct.v6n2p13
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Use of Film and Television Documentary: Sugihara, Conspiracy of Kindness

Abstract: Film or television documentary can serve a unique role in the curriculum and teaching of courses in political science and history where the complexity of the human element such as interaction, motive, identity and ethical position require analysis. The documentary Sugihara, Conspiracy of Kindness, a film by Kirk and Vicari, first screened on May 5, 2005 on PBS, can in a qualitative sense positively demonstrate this role. The negative side to the use of film and television documentary is also noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The works of teachers or the available media are supposed to be maximized by teachers to improve the interest and learning achievements of learners. UNESCO revealed that various computer-based technology has been utilized, such as to distribute lesson plans through CD-ROM's, arrange exchange programs through computer-conferences among schools and teachers, encourage the utilization of web-based materials, and use computer conferences to encourage discussions among learners (Nasrullah, 2014;Bostock, 2017).…”
Section: Task and Responsibilities Of Teachers In Learning Process Standard Completionmentioning
confidence: 99%
“…The works of teachers or the available media are supposed to be maximized by teachers to improve the interest and learning achievements of learners. UNESCO revealed that various computer-based technology has been utilized, such as to distribute lesson plans through CD-ROM's, arrange exchange programs through computer-conferences among schools and teachers, encourage the utilization of web-based materials, and use computer conferences to encourage discussions among learners (Nasrullah, 2014;Bostock, 2017).…”
Section: Task and Responsibilities Of Teachers In Learning Process Standard Completionmentioning
confidence: 99%